Forensic Pathologist’s Dilemma in the wake of COVID-19 Pandemic - Khajuria, Himanshu; Nayak, Biswa P (Acta Biomedica Atenei Parmensis, 2021)
The role of forensic pathologist is imperative for investigation of pathophysiological outcome of disease by conducting autopsy or post-mortem examination. Autopsy examination becomes highly significant when the cause of death is unknown or physicochemical parameters of death is of unknown nature due to novel emerging conditions as in case of novel coronavirus pandemic. In the wake of COVID-19 pandemic, there is undeniable amount of pressure on the forensic examiner fraternity due to the highly contagious nature of new coronavirus (SARS-CoV-2). Autopsy involves thorough external examination of the deceased body followed by gross internal, histopathological examination of organs and molecular analysis of body fluids for various tissue specific and blood biomarkers (enzymes, electrolytes, hormones) to ascertain disease progression and cause of death.